Proceedings of the Australian National Playwrights Conference, Canberra, 1973. - Australian National Playwrights Conference 1973 : Canberra, A.C.T.) (1973)
This conference provided a forum for playwrights to discuss their craft with a critical examination of a selection of plays.
Reel 1. Horses / Finola Moorehead -- Reel 2. The after-life of Arthur Cravan / Alma De Groen -- Reel 3. It isn't cricket / Robert Lord -- Reel 4. Conference papers and Australian National Playwrights administrative discussions -- Reel 5. Critics' forum -- Reel 6: Side 1. The after-life of Arthur Cravan / Alma De Groen - Side 2. Carillo Ganter leads a discussion on the Australian Council for the Arts -- Reel 7. Overture / Mark O'Connor - A new Mary Xmas / Stuart Dickson - Informal critical discussion - It isn't cricket / Robert Lord -- Reel 8.: Side 1. Official opening of the inaugural Australian National Playwrights Conference / Lew Luton, Margaret Whitlam, G. C. White - Address and discussion / John Sumner - Address and discussion / Googie Withers - Side 2. Discussions with Irene Innescourt, Barry Barkla, Tony Llewellyn-Jones, Frank Thring -- Reel 9. Australian National Playwrights Conference seminar, 11 March -- Reel 10. Informal discussion.
Recorded beween 5-18 March 1973 in Childers Hall at the Australian National University, Canberra, A.C.T.
Digital master available
Related material: Papers of the Australian National Playwrights Conference held by National Library of Australia Manuscripts Section at MS 5062.
Summary not yet available.
Keywords: Playwriting -- Australia -- Congresses; Theater -- Production and direction -- Australia; Dramatists, Australian -- Congresses; Drama -- Technique; Australian drama -- History and criticism